2015
DOI: 10.1590/1806-9282.61.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells: a new approach to tumor development

Abstract: Kobayashi NCC et al. 86rev assoC Med bras 2015; 61(1):86-93

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The percentage of peritoneal MCAs increased proportionally to the increased concentration of chemotherapeutic agents within a 72-h period. Efficient tumorigenesis in vivo is the most important feature of cancer stem cells 22 . We selected 6 samples of peritoneal MCAs from 14 samples to perform a tumorigenicity assays in nude mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of peritoneal MCAs increased proportionally to the increased concentration of chemotherapeutic agents within a 72-h period. Efficient tumorigenesis in vivo is the most important feature of cancer stem cells 22 . We selected 6 samples of peritoneal MCAs from 14 samples to perform a tumorigenicity assays in nude mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In solid tumors, tumor stem cells were detected for the first time in a breast tumor by Al-Hajj et al, 21 and exhibit characteristics of self-renewal, differentiation, increased membrane permeability, migration capacity, and antiapoptotic activity. 22,23 Thus, a specific subset of tumor cells with stem cell characteristics may play a role in tumor initiation, progression, and recurrence. 23,24,25 Tumor stem cells and associated proteins have been investigated in some oral neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Thus, a specific subset of tumor cells with stem cell characteristics may play a role in tumor initiation, progression, and recurrence. 23,24,25 Tumor stem cells and associated proteins have been investigated in some oral neoplasms. 26 Recent studies on head and neck squamous cell carcinoma indicated an important role of tumor stem cells in tumor development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that minimum amount of cancer stem cells can lead to disease relapse, and removal of cancer stem cells would mean the eradication of the disease. However, the major hurdle is to find treatments that can kill these specific stem cells without harming the normal cells[38]. The screening of cancer stem cells can be used to prognosticate the severity of OSSN and possibly its metastatic potential.…”
Section: Discussionmentioning
confidence: 99%